Enhancing Scientific Creativity through STEM-Based Flipbooks: A Study on Environmental Changes - Desylva Nikita Jasmine; Indri Yani; Desti Herawati (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
This study investigates the development and effectiveness of a STEM-based flipbook designed to enhance students’ scientific creativity in biology, specifically focusing on environmental change topics. Scientific creativity is increasingly vital in addressing technological and societal challenges, prompting the integration of STEM elements into educational materials. The flipbook was developed using the ADDIE model, encompassing five stages: analysis, design, development, implementation, and evaluation. During the design stage, STEM components—science, technology, engineering, and mathematics—were embedded to support student engagement and understanding. The research involved 31 Grade X students and utilized pre-test and post-test assessments to measure the impact on scientific creativity skills. Data analysis was conducted using quantitative descriptive methods and SPSS software for statistical testing. Expert validation indicated excellent content and media quality (95% and 97.5%, respectively), affirming the flipbook’s educational relevance. Results showed a significant improvement in students’ scientific creativity, with average scores rising from 71.4 to 90.4 and an N-Gain of 0.44, categorized as moderate. The Wilcoxon test yielded a p-value of 0.001, indicating statistically significant improvement. Teacher and student responses were highly positive, with 100% and 85% satisfaction ratings, respectively. These findings suggest that STEM-based flipbooks can effectively enhance students’ creative thinking and problem-solving skills in biology. The study concludes that interactive STEM-integrated materials are valuable tools for fostering 21st-century skills and recommends broader implementation in science education to improve learning outcomes and student engagement.